A single plan solution to chest wall radiotherapy with bolus? - Ordonez-Sanz, C (The British Institute of Radiology., 2014)
OBJECTIVE: Radiotherapy treatments of post-mastectomy chest walls are complex, requiring treatment close to skin, necessitating bolus use. Commonly used 5- and 10-mm-thick boluses develop full skin dose, needing removal for the latter half of treatment and requiring two treatment plans to be generated. Can a thinner bolus be used for all treatment fractions, requiring only one plan? METHODS: Investigation of doses received using (A) a half-time 10-mm-thick Vaseline® bolus (current situation); (B) a brass mesh (Whiting & Davis, Attleboro Falls, MA) and (C) 3- and 5-mm Superflab™ (Mick Radio-Nuclear Instruments, Mount Vernon, NY) for 6 and 15 MV. Dosimetric measurements in Barts WT1 solid water and an anthropomorphic phantom, using ionization chambers and thermoluminescent dosemeters, were used to study the effect of different bolus regimes on the photon depth–dose curves (DDCs) and skin doses. RESULTS: Measured skin doses for the current 10-mm-thick Vaseline bolus, brass mesh and 3-mm bolus were compared (5 mm bolus has been rejected). The brass mesh has the least effect on the DDC, with changes <0.7% for depths greater than d(max). Brass mesh conforms superiorly to skin surfaces. Measurements on an anthropomorphic phantom demonstrate an increased skin dose compared with our current treatment protocol. CONCLUSION: Brass mesh has the smallest effect on the DDC, whilst sufficiently increasing surface dose. It can be removed at any fraction, based on a clinical decision, without the need for generating a new plan. Treating with one plan significantly reduces planning times. ADVANCES IN KNOWLEDGE: Quantification of skin doses required and achieved from wax-on/wax-off treatment compared with alternative available breast boluses.